2022
DOI: 10.1590/0001-3765202220210795
|View full text |Cite
|
Sign up to set email alerts
|

Response of southern troposphere meridional circulation to historical maxima of Antarctic sea ice

Abstract: The variability of Antarctic sea ice (ASI) has great potential to affect atmospheric circulation, with impacts that can extend from the surface to the middle and high levels of troposphere. The present study has evaluated the response of South Atlantic tropospheric circulation to increased coverage in area and volume of ASI. Monthly data of air temperature, zonal and meridional wind and mean sea level pressure were obtained from two ensemble simulations performed with the GDFL/CM2.1 model, covering the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…. These patterns align with the typical characteristics of zonal wind in the AAO positive phase and are in line with previous research findings (Azhar et al, 2022;Queiroz et al, 2022). Additionally, the structures of the anomalous zonal averaged winds are corresponding to the local vertical meridional cells.…”
Section: Journal Of Geophysical Research: Atmospheressupporting
confidence: 92%
See 1 more Smart Citation
“…. These patterns align with the typical characteristics of zonal wind in the AAO positive phase and are in line with previous research findings (Azhar et al, 2022;Queiroz et al, 2022). Additionally, the structures of the anomalous zonal averaged winds are corresponding to the local vertical meridional cells.…”
Section: Journal Of Geophysical Research: Atmospheressupporting
confidence: 92%
“…As depicted in Figure 8b, the zonal averaged wind anomalies in vertical direction display a barotropic nature, characterized by an increase in zonal wind near 60°S and a decrease near 35°S. These patterns align with the typical characteristics of zonal wind in the AAO positive phase and are in line with previous research findings (Azhar et al., 2022; Queiroz et al., 2022). Additionally, the structures of the anomalous zonal averaged winds are corresponding to the local vertical meridional cells.…”
Section: Observation Analysissupporting
confidence: 90%
“…Upward anomalies are displayed between 40° and 30°S and downward at 50°–40°S (Figure 5b), indicating a weakening of the Ferrel cell. Queiroz et al (2022) found similar behaviour of Hadley and Ferrel cells. A maximum southward anomaly over the upper troposphere between 40° and 30°S corroborated the same results (Figure 5a).…”
Section: Resultsmentioning
confidence: 73%
“…According to Ciasto and Thompson (2008), large‐scale atmospheric variability in the Southern Hemisphere is mainly driven by two climate variability modes: the Southern Annular Mode (SAM) and the El Niño–Southern Oscillation (ENSO). On an interannual timescale, the interaction between these modes generates SST anomalies in the South Atlantic Ocean that contribute to the South American climate (Andreoli & Kayano, 2006; Parise et al, 2022; Queiroz et al, 2022; Rudeva & Simmonds, 2015; Silva & Ambrizzi, 2006; Torres et al, 2022; Vasconcellos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%